(untitled) (Linguistics in Amsterdam, 2021)
In this paper the authors attempt to make some inroads into compiling a survey of expressions of past tense habituality across Slavic languages – to date a lacuna. Slavic languages share an aspectual system that is binary (perfective opposes imperfective) and lack a specific habitual aspect. Nevertheless, aspect does play a part in the expression of habituality, which is not restricted to imperfective verbs. That said, habituality usually “arises” in context and needs to be studied as such, also in order to establish its actual nature: a matter that we will only be able to touch upon. The starting point of our inventory is twofold: first we attempt to demonstrate the different use of the aspects in the context of a past narrative passage from Bulgakov’s The Master and Margarita, and point out the variety of aspect choice amongst Slavic languages in situations of habituality. Then we list and discuss expressions sourced from the available literature and some own research. Especially as specific studies into habituality for quite a few Slavic languages are lacking to date, this contribution is not exhaustive.